Effect of tree-level and mean-field improvement on the light-hadron spectrum in quenched QCD - RYAN, SINEAD MARIE (American Physical Society, 1997)
We compute the light-hadron mass spectrum at b55.7 using the O(a)-improved Sheikholeslami-Wohlert fermion action with two choices of the clover coefficient: the classical value c51 and a mean-field or tadpole-improved estimate c51.57. We compare our results with those of the GF11 Collaboration who use the Wilson fermion action (c50). We find that changing c from zero to 1 and 1.57 leads to significant differences in the masses of the chirally extrapolated and strange pseudoscalar and vector mesons, the nucleon, the D, and also in the Edinburgh plot. A number of other quantities, for example, mV 2 2mP 2 , J, amK /amr , and amK* /amr do not appear to change significantly. We also investigate the effect of changing the lattice volume from approximately ~2 fm!3 to ~2.6 fm!3. We find that the meson masses are consistent to within one standard deviation and baryon masses are consistent to within two standard deviations. PACS number~s!: 12.38.Gc, 11.15.Ha, 14.65.Bt
PUBLISHED
Keywords: Pure & Applied Mathematics